Heart Failure in Clinical Practice - Henein, Michael Y.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Over the years, there has been considerable progress in the diagnosis and management of the syndrome of heart failure, the end-stage of most cardiac diseases. While the outlook for heart failure patients is significantly improved, little has yet been achieved in prevention of the condition and much remains to be done to delay disease progression and alleviate symptoms. This cannot be achieved without further high quality research, particularly into the causes of heart failure itself and its progression from other less serious conditions. As heart failure is commonly increasing, there is a need for all medical practitioners to be aware of the early signs and symptoms so early diagnosis and appropriate management can be offered. Heart Failure in Clinical Practice provides a toolkit for clinicians to guide them in the diagnosis and treatment of patients with suspected heart failure. Algorithms and flow diagrams are included to give the reader an illustrated snapshot of the decisions involved in the management of these patients. The more controversial issues mentioned in the chapters of this book aim to stimulate clinicians to progress these ideas.
Definition, Diagnosis, Epidemiology, Etiology and Pathophysiology of Heart Failure -- Inherited Myocardial Diseases -- Valvular Heart Disease in Heart Failure -- Congenital Heart Disease -- Heart Failure with a Normal Ejection Fraction -- Right Heart Failure -- Pulmonary Arterial Hypertension -- Cardiac Cachexia in Chronic Heart Failure: The Metabolic Facet of CHF -- Breathing Disturbances in Heart Failure -- Stress Echocardiography -- Echocardiography in Heart Failure -- Cardiac Radionuclide Imaging in the Assessment of Patients with Heart Failure -- Cardiovascular Magnetic Resonance in Heart Failure -- Principles of Treatment and Pharmacotherapy -- Nonpharmacological Therapies -- Atrial Fibrillation and Heart Failure Syndromes -- Natriuretic Peptides -- Cardiac Resynchronization Therapy -- Device Therapy in Heart Failure -- The Role of Surgery in Heart Failure.
Keywords: Medicine; Emergency medicine; Public health; Internal medicine; Cardiology; Diabetes; Medicine & Public Health; Cardiology; Internal Medicine; Emergency Medicine; Health Promotion and Disease Prevention; Public Health; Diabetes